Real-time clinical alerting: effect of an automated paging system on response time to critical laboratory values—a randomised controlled trial. Issue 2 (29th March 2010) - Etchells, E; Adhikari, N KJ; Cheung, C; Fowler, R; Kiss, A; Quan, S; Sibbald, W; Wong, B
Abstract : Background: Timely and reliable communication of critical laboratory values is a Joint Commission National Patient Safety Goal. The objective was to evaluate the effect of an automated system for paging critical values directly to the responsible physician. Methods: A randomised controlled trial on the general medicine clinical teaching units at an urban academic hospital was conducted from February to May 2006; the unit of randomisation was the critical laboratory value. The intervention was an automated paging system that sent the critical value directly to the responsible physician's pager. The control arm was usual care, which was a telephone call to the patient's ward by the laboratory technician. The primary outcome was response time, defined as the interval between acceptance of the critical value into the laboratory information system to the writing of an order on the patient's chart in response to the critical value. If the time of order was not documented, the time of administration of treatment was used to calculate response time. Results: For primary analysis, 165 critical values were evaluated on 108 patients with full response time data. The median response time was 16 min (IQR 2–141) for the automated paging group and 39.5 min (IQR 7–104.5) for the usual care group (p=0.33). Conclusions: The automated paging system reduced the length of time physicians took to respond to critical laboratory values, but this difference was not statistically significant. Future reseach should evaluate the effects of alerts for conditions that currently do not generate a phone call and the addition of real-time decision support to the critical value alerts.